Development of tutorial video media of silent meditation technique to reduce students’ symptoms stress in learning at UPT SMPN 9 binamu - AR, Nafilah Amaliah; Mansyur, Ahmad Yasser; Latif, Suciani; Buchori, Sahril (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
The purpose of this study was to find out (1) An overview of the needs for developing video tutorial media for silent meditation techniques to reduce student learning stress at UPT SMPN 9 Binamu, (2) Prototype video tutorial media for silent meditation techniques to reduce student learning stress at UPT SMPN 9 Binamu, (3) Validity and practicality of video tutorial media for silent meditation techniques to reduce student learning stress at UPT SMPN 9 Binamu. This research uses the Research and Development (RnD) method with the Borg and Gall development model modified by the researcher. The subjects of this study were subjects in the needs analysis 24 students, subjects in the validity test 2 expert and subjects in the practicality test 10 students. The types of data collection instruments used are needs analysis data, validity data, and practicality data. The data analysis techniques used are needs questionnaire analysis, validity questionnaire analysis, and practicality questionnaire analysis. The results showed that the video tutorial media for silent meditation techniques and guidebooks developed were valid and practical for use in providing guidance and counseling services at UPT SMPN 9 Binamu, based on the acceptability test which includes usefulness, feasibility and accuracy.